Does the Serum Vaspin Level Have a Role in the Diagnosis of Primary Ovarian Insufficiency? - Koyun, Fatma Nur; Yilmaz, Nafiye; Tugrul Ersak, Duygu (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: This study was designed to compare the serum vaspin levels between patients with primary ovarian insufficiency (POI) and healthy fertile women. STUDY DESIGN: Sixty-nine patients diagnosed with idiopathic POI and 70 age-matched healthy fertile women were included in this case-control study. General gynecological and physical examination findings and serum basal hormone levels were recorded. Vaspin levels in serum samples were determined using the Enyzme-Linked ImmunoSorbent Assay (ELISA) method. RESULTS: The mean age of the patients with POI was 31.9±5.4 years, while it was 31.2±3.8 years in the control group. There were no statistically significant differences in body mass index, gravidity, parity, and cigarette consumption between the groups. However, the mean follicle-stimulating hormone level in POI patients was 55.4±25.1 IU/L, significantly higher than the 6.2±1.8 IU/L observed in the control group. Luteinizing hormone levels were also significantly higher in POI patients, while estradiol and anti-Mullerian hormone values were significantly lower. Furthermore, the mean serum vaspin level in POI patients was 0.79±0.56 ng/mL, compared to 1.08±0.64 ng/mL in the control group (p<0.001). CONCLUSIONS: Serum vaspin levels were found to be decreased in women with POI. Therefore, monitoring the serum vaspin levels in women with POI may help in the early identification of patients with POI.